A Comprehensive Model for Hardness Evaluation of Low-Alloy Steels Based on Carbon Content and Ultrasonic Wave Velocity - Uzun, Fatih; Bilge, Ali Nezihi (Amer Soc Nondestructive Test, 2017)
Ultrasonic techniques allow for the nondestructive investigation of material properties including hardness, but the requirement of correlation for each material, such as different alloys of steel, separately turns these tasks into a formidable process. This study aims to overcome this problem by proposing a new technique for hardness evaluation of low-alloy steels based on ultrasonic wave velocity and information about the weight percent of carbon content. For this purpose, carbon steel samples with different carbon content, less than 0.5 wt%, were selected. Samples were annealed at varying temperatures, and then an immersion ultrasonic technique was used to measure longitudinal ultrasonic wave velocity in each sample. The hardness of annealed samples was determined on the rockwell B scale. The relationship between ultrasonic wave velocity and hardness of annealed steel samples was investigated in terms of carbon content. A mathematical model was developed, based on carbon content and ultrasonic wave velocity, to predict hardness.
Keywords: Annealing; Hardness; Ultrasonic Wave Velocity; Longitudinal Waves; Low-Alloy Steel; Steel Carbon Content; Austenitic Stainless-Steel; Electron-Beam Irradiation; Mechanical-Properties; Annealing Behavior; Grain-Size; Microstructure; Temperature; Stability; Sheet